학교모래놀이 집단상담이 자해경험이 있는 초등학생의 자아개념, 자해 기능, 자살사고에 미치는 효과: 예비연구 - 전문주; 이호경; 안운경 (심리상담 및 모래놀이치료(구 학교상담 및 모래놀이), 2023)
본 연구는 자해 경험이 있는 초등학생 집단을 대상으로 자아개념, 자해 기능, 자살사고 측면에서 학교모래놀이 집단상담의 효과를 알아보고자 하였다. 충남 아산시 소재 A초등학교 재학생 중 Wee클래스 상담에서 자해 경험을 보고한 학생 6명을 연구대상으로 선정하였으며 2021년 9월부터 11월까지 총 10회기의 집단상담을 실시하였다. 집단상담의 효과검증을 위해 한국판 소아 자기개념척도(PHCSS), 한국판 자해 기능 평가지(FASM), 한국판 청소년 자살사고설문지(SIQ-JR)를 측정도구로 사용하였으며 SPSS 21.0 프로그램을 사용하여 Wilcoxon signed-ranks test를 실시하고 효과크기를 산출하였다. 분석 결과 자해 기능의 자해 빈도(z=-2.207, p=.027, Cohen's d=0.14)와 내적 동기 척도(z=-2.032, p=.042, Cohen's d=1.15)가 유의하게 감소하였다. 이러한 결과는 학교모래놀이 집단상담이 자해 빈도를 감소시키는 효과적인 방법일 수 있음을 시사한다. This study attempted to investigate the effect of group counseling for school sand play in terms of self-concept, self-injury function, and suicide ideation for elementary school students with self-injury experience. Among the students of A Elementary School in Asan-si, six students who reported their self-injury experiences in Wee-class counseling were selected as subjects of the study, and a total of 10 group counseling sessions were conducted from September to November 2021. To verify the effectiveness of group counseling, Piers-Harris Children′s Self-Concept Scale-Korean Version (PHCSS), The Functional Assessment of Self-Mutilation-Korean Version (FASM), and Suicidal Ideation Questionnaire-JR-Korean Version (SIQ-JR) were used as measurement tools, and Wilcoxon signed-ranks test was performed using the SPSS 21.0 program and the effect size was calculated. As a result of the analysis, the scale of self-injury frequency(z=-2.207, p=.027, Cohen's d=0.14) and internal motivation(z=-2.032, p=.042, Cohen's d=1.15) of the self-Mutilation function was significantly reduced. These results suggest that school sand play group counseling can be an effective way to reduce self-injury frequency. KCI Citation Count: 1